2021
DOI: 10.1038/s41598-021-93962-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic overlap and causal associations between smoking behaviours and mental health

Abstract: Cigarette smoking is a modifiable behaviour associated with mental health. We investigated the degree of genetic overlap between smoking behaviours and psychiatric traits and disorders, and whether genetic associations exist beyond genetic influences shared with confounding variables (cannabis and alcohol use, risk-taking and insomnia). Second, we investigated the presence of causal associations between smoking initiation and psychiatric traits and disorders. We found significant genetic correlations between s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 98 publications
(103 reference statements)
2
19
0
Order By: Relevance
“…One retrospective study reported that 90% of patients with SCZ started smoking before the onset of their disease (Kelly & McCreadie, 1999), and longitudinal studies have pointed out that cigarette smoking increases the risk of developing SCZ and consistently reported a dose-response relationship of smoking quantity (Kendler et al, 2015;McGrath et al, 2016;Mustonen et al, 2018;Weiser et al, 2004). A previous MR study with 632,802 Caucasian population of smoking initiation GWAS also supported our finding, which indicated a causal role of smoking initiation in many psychiatric disorders, including SCZ, depression, and bipolar disorder (Barkhuizen et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…One retrospective study reported that 90% of patients with SCZ started smoking before the onset of their disease (Kelly & McCreadie, 1999), and longitudinal studies have pointed out that cigarette smoking increases the risk of developing SCZ and consistently reported a dose-response relationship of smoking quantity (Kendler et al, 2015;McGrath et al, 2016;Mustonen et al, 2018;Weiser et al, 2004). A previous MR study with 632,802 Caucasian population of smoking initiation GWAS also supported our finding, which indicated a causal role of smoking initiation in many psychiatric disorders, including SCZ, depression, and bipolar disorder (Barkhuizen et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent and strong evidence has been reported for the causal effect of smoking initiation on SCZ among European-origin individuals (Barkhuizen et al, 2021; Gage et al, 2017; Wootton et al, 2020; Yuan et al, 2020); however, this issue has been less discussed in the Asian populations. Only one MR analysis in Asian participants with limited statistical power reported no significant causal association between smoking and SCZ (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Different non-mutually exclusive mechanisms have been proposed to explain the link between tobacco smoking and mental health symptoms, including biological explanations such as nicotine-induced elevated dopamine release ( 6 , 43 ) and shared genetic vulnerability ( 44 ). On the behavioral level, both maladaptive coping and misattribution are thought to play a key role in the relationship between smoking and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Mendelian randomization approach is not biased by reverse causation or confounding when assuming that genetic instruments are directly associated with the exposure, genetic instruments are not related to confounders, and no pleiotropy is allowed from genetic instruments to outcome. Previous Mendelian randomization studies have suggested that smoking shows causal effect on schizophrenia, and vice versa 13 16 . However, most studies were conducted in Caucasian populations with a sufficient sample size for GWASs for smoking and schizophrenia.…”
Section: Introductionmentioning
confidence: 98%